Mendeley Application Training for Teachers of MI Humaira - Kristiawan, Muhamad; Yanti, Fitri April; Kurniawan, Rio; Siska, Jumiati; Viona, Elsa (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
Many instructors do not use automatically quoting and producing bibliographies, the present service is attempting to assist teachers in using the Mendeley program. This workshop seeks to increase MI Humaira instructors' abilities to cite and write bibliographies using the Mendeley program. The course takes a performance-based approach, although it begins with explaining and providing examples before assisting with installation and sync to Microsoft Word. There were 20 instructors from MI Humaira who took part in this training. The outcome of this exercise was that the participants were able to master Mendeley when writing scientific articles.